Reducing the Incidence of Suicide in Indigenous Groups - Strengths United through Networks 2015-2017 - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group, 2017)
RISING SUN was designed to develop a toolkit comprised of the key correlatesa ssociated woth successful suicide prevention interventions across Arctic States. The principal goal was to generate shared knowldegt o aid health and community workers in better serving their communities, and to help policy-makers measure progress, evaluate interventions, and identify regional and cultural approaches to implementation. Under the US Arctic Council Chairmanship theme of Improving Economic and Living Conditions in Arctic Communities, the RISING SUN initiative used a consensus-building process to identify common outcomes and their measures for evaluating suicide prevention efforts across the circumpolar North.